Obsessive-Compulsive Disorder The Old and the New Problems - Kalinin, Vladimir (IntechOpen, 2014)
Although Obsessive-Compulsive Disorder (OCD) has been known since the ancient times, the exact etiology and pathogenesis of OCD unfortunately still remain unknown. In addition, the therapeutic approaches elaborated for the treatment of OCD as a whole are not perfect, and this disorder as a rule is characterized by unfavorable course and lack of full therapeutic response. In the current book some modern data on pathogenesis, phenomenology and treatment of OCD are presented. Besides, the data on co-morbidity of OCD with other neurological and psychiatric disorders are also included. This book is intended for broad circle of readers, but mostly for psychiatrists, psychologists and neurologists.